2021
DOI: 10.1007/s11892-021-01377-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution to Non-alcoholic Fatty Liver Disease and Prognostic Implications

Abstract: Purpose of Review Non-alcoholic fatty liver disease (NAFLD) is a major and increasing health burden, with the potential to overwhelm hepatology services. However, only a minority of patients develop advanced liver disease. The challenge is early identification of patients at risk of progression. This review aims to summarize current knowledge on the genetic predisposition to NAFLD, and its implications for prognostication and risk stratification. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…Literature data indicate that the pathogenesis of NAFLD is closely linked with increased adiposity, dyslipidemia, and insulin resistance [9]. Recently, the influence of genetic factors in the development of hepatic steatosis, as well as its progression in more severe forms of liver disease, has been reported in both experimental and observational studies [10,11]. Genome wide association studies (GWAS) have demonstrated the presence of genetic variants associated with NAFLD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data indicate that the pathogenesis of NAFLD is closely linked with increased adiposity, dyslipidemia, and insulin resistance [9]. Recently, the influence of genetic factors in the development of hepatic steatosis, as well as its progression in more severe forms of liver disease, has been reported in both experimental and observational studies [10,11]. Genome wide association studies (GWAS) have demonstrated the presence of genetic variants associated with NAFLD [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant heterogeneity in the clinical phenotype and natural history of NAFLD because it is a multifactorial disease resulting from the interaction between the genetic background and environmental factors ( 4 ). Obesity, type 2 diabetes, reduced physical activity, and genetic variants are the most important risk factors; however, it is unclear which of them plays a decisive role in the disease promotion and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, type 2 diabetes, reduced physical activity, and genetic variants are the most important risk factors; however, it is unclear which of them plays a decisive role in the disease promotion and progression. Therefore, in clinical practice, it is unknown which patients have the greatest risk of suffering from liver damage or developing liver cirrhosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of non-invasive methods have been developed by combining clinical and serological variables that are able to determine the occurrence of advanced fibrosis in patients with NAFLD. 13 NAFLD fibrosis score (NFS) is one of the non-invasive methods that has been validated in its application for determining the degree of liver fibrosis in patients with NAFLD. NFS has been recommended by the American Association for Study of Liver Disease (AASLD), American College of Gastroenterology (ACG), American Gastroenterological Association (AGA) and by the European Association for the Study of the Liver (EASL).…”
Section: Introductionmentioning
confidence: 99%
“…NFS has been recommended by the American Association for Study of Liver Disease (AASLD), American College of Gastroenterology (ACG), American Gastroenterological Association (AGA) and by the European Association for the Study of the Liver (EASL). 13,14 NAFLD is known to be a risk factor for the occurrence of subclinical abnormalities in myocardial metabolism and is associated with subclinical changes over time in left ventricular structure function, which causes both structural and functional heart abnormalities. 14 Left ventricular mass index (LVMI) is an adjusted mass of the left ventricle to the total surface area of the body.…”
Section: Introductionmentioning
confidence: 99%